The role of proximity relations in regional and territorial development processes - André Torre; Fred Wallet (European Regional Science Association (ERSA), 2014)
Proximity analyses have nowadays turned out to be a part of the toolbox of regional scientists and this notion recently became very popular in the position of politics, and private or public stakeholders. In parallel, the notion of proximity spread in the academic literature and is now commonly used by scholars in regional science, geography or spatial economics. Interest is affecting now the works dedicated to innovation process, links between science and industry, relations between users and producers or sub-contractors, national systems of innovation, innovative milieus, about also local labour markets or urban policies. But despite the substantial literature on proximity processes and relations, only a few academic works have been devoted to studying the link between regional development and proximity relations. We consider that the integration of the notion of proximity into the framework of regional development analysis provides interesting input due to its plasticity and ability to draw connections between spatial, economic and social dimensions; but also suggests ways of possible changes for regional and territorial policies. The main outline is to try to assess the importance of proximity relations (or obstacles led by proximity relations) in regional development processes, and discuss approaches of different disciplines. We aim to re-situate the analysis of proximity within the various theoretical approaches to the territory and, in particular, to highlight its place and the role it could play in the study of regional and territorial development processes, and possibly its contribution to public policies or collective action. It seems interesting to investigate the relation between proximity analyses and regional or local and territorial development; taking into account long distance relations and clusterisation processes has led to a renewal of development approaches. This investigation consists of three main axes of inquiry related to the ability to go beyond the sterile opposition between the local only and the decisive influence of distance relations. Are the themes addressed in these approaches wide and diverse enough to account for the mechanisms that reflect the diversity and complexity of the processes of local development (or are they, on the contrary, too specific to certain areas)? Are the (conceptual and analytical) tools, models and applied (qualitative and quantitative) studies based on an analysis of the phenomena of regional development through proximity sufficiently robust and objectifiable (and can they be used to generate valuable measures)? Can the results of proximity based analyses be translated into recommendations for decision-making and coordination between stakeholders, including in the field of public action or policies?
Keywords: R1; R5; 330; Regional development; proximity; innovation; governance